Making sense of Nordicness, or making Nordicness? - Kristine Ask; Marie Antonsen; Anja Johansen (Nordic Journal of Science and Technology Studies, 2016)
What is Nordic? Does it make sense to talk about Nordic Science and Technology Studies (STS)? If so, what kind of contributions could Nordic perspectives give to global STS and other disciplines? And what elements of the international field of STS are being developed and honed by Nordic scholars?